2019
DOI: 10.1002/jcb.29117
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR‐623 suppresses progression of hepatocellular carcinoma via regulating the PI3K/Akt signaling pathway by targeting XRCC5

Abstract: It has been reported that miR‐623 is deregulated in lung adenocarcinoma and inhibits tumor growth and invasion. However, it is unclear whether miR‐623 has a role in the progression of hepatocellular carcinoma (HCC). Herein, we found that miR‐623 was significantly downregulated in HCC, and that its expression was related to poor clinical outcomes of patients with HCC. Upregulation of miR‐623 decreased cell proliferation, viability, migration, and invasion and further promoted apoptosis in 7721, Huh7, and Bel‐74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…manifested that miR-623 inhibited pancreatic cancer metastasis in vitro and in vivo through targeting matrix metalloproteinase-1 (MMP1) [ 16 ]. Ren and colleagues illuminated that miR-623 functioned as a tumor suppressor in hepatocellular carcinoma through modulating the phosphoinositide 3‐kinase/protein kinase B (PI3K/Akt) pathway via targeting X-ray repair cross complementing 5 (XRCC5) [ 27 ]. In the current study, our data demonstrated that low miR-623 level was associated with a poor clinical outcome of GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…manifested that miR-623 inhibited pancreatic cancer metastasis in vitro and in vivo through targeting matrix metalloproteinase-1 (MMP1) [ 16 ]. Ren and colleagues illuminated that miR-623 functioned as a tumor suppressor in hepatocellular carcinoma through modulating the phosphoinositide 3‐kinase/protein kinase B (PI3K/Akt) pathway via targeting X-ray repair cross complementing 5 (XRCC5) [ 27 ]. In the current study, our data demonstrated that low miR-623 level was associated with a poor clinical outcome of GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, miR-623 could repress cell proliferation and invasion via decreasing X-ray repair 1036 cross complementing 5 (XRCC5) in hepatocellular carcinoma. 13 These reports all indicated the anti-tumor role of miR-623 in many cancers. Importantly, Wei et al reported that miR-623 could reduce cell proliferation and metastasis via decreasing Ku80 in lung adenocarcinoma, a major type of NSCLC.…”
Section: Discussionmentioning
confidence: 95%
“…10 MiR-623 has been reported that could reduce tumor growth and metastasis in human cancers, such as gastric cancer, pancreatic cancer and hepatocellular carcinoma. [11][12][13] Moreover, miR-623 could repress NSCLC progression via targeting Ku80 and inactivating the extracellular signal-related kinase (ERK)/c-Jun N-terminal kinase (JNK) pathway. 14 Nevertheless, whether miR-623 is required for circZNF609 in NSCLC development is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…31 High XRCC5 expression had been confirmed to promote HCC proliferation and metastasis, and could predict patients' poor prognosis. 32,33 Our data At present, the role of exosomes in cancer has received more and more attention, and exosomal circRNAs have shown great advantages in the treatment and diagnosis of cancer. 20 In this, we found that circANTXR1 was expressed in exosomes from HCC cells, and the overexpressed exosome circANTXR1 promoted HCCLM3 cell proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 77%